Manajemen Media Pimpinan Cabang Muhammadiyah dalam Penanaman Nilai Akhlak pada Anak-anak di Sigambal Kecamatan Rantau Selatan Kabupaten Labuhanbatu - Rafly Prahmana Hidayat; Hasnun Jauhari Ritonga (UMSU, 2022)
The purpose of conducting this research is to find out the media management of the Muhammadiyah Branch Leaders in instilling moral values in children in Sigambal, Rantau Selatan District, Labuhanbatu Regency. This research is a research that uses qualitative descriptive research methods that are directed at symptoms, facts, or events regarding certain characteristics, populations, or areas in a systematic and accurate manner. From the results of this study it was revealed that, instilling good moral values in children was carried out using film or video media (watching together). Watching Together (NOBAR) is an activity of watching a show together in an association or group, a place that is used freely, such as at home, at school, or in a cinema. The findings of this study prove that media management carried out by the Sigambal Muhammadiyah Branch Manager, Rantau Selatan District, Labuhanbatu Regency has a very large positive impact on the surrounding community, in shaping good behavior in children in the current era of globalization. Film or video media (watching together) is the media used by the Sigambal Muhammadiyah Branch Manager, South Rantau District, Labuhanbatu Regency in instilling moral values and drawing the focus of children's attention to participate actively in the formation of good behavior. This research also hopes that children will be motivated and always to behave and behave well in everyday life.